Exploring Sea Country through high-resolution 3D seismic imaging of Australia's NW shelf: Resolving early coastal landscapes and preservation of underwater cultural heritage. (1st July 2020) - O'Leary, Michael J.; Paumard, Victorien; Ward, Ingrid
Abstract: Almost 2 million square km of Australia's continental shelf was flooded following the termination of the last glacial maximum, and with it the cultural heritage of the first arrival and coastal occupation of Australia beginning some 65, 000 years ago. In order to prospect for this missing cultural record, we must first identify submerged coastal landscapes and landforms that likely provided favourable environments for occupation and resource use. However, this task is challenged by the sheer size of the Australian continental margin. To help address this, we use industry 3D seismic datasets, that cover vast areas of Australia's continental shelf, to map seafloor bathymetry at high resolution (10–25 m). Our study focuses an area of 6500 square km on the mid/outer shelf regions proximal to Barrow Island. The 3D seismic bathymetry revealed a highly complex and geomorphically mature coastal landscape preserved at depths of 70–75 m below sea level, including coastal barrier dunes, lagoonal systems, tidal flats and estuarine channels. Based on the depth of the submerged shorelines and reconstructed sea level curves, the age range of these coastal landforms is constrained to Marine Isotope Stage 3 (57–29 ka), which overlaps with the known onset of occupation at Barrow Island and the wider Carnarvon bioregion and the adjacent Pilbara. Such feature preservation has significant geoheritage value, but also allows for human behavioural ecology modelling and provides targets for future dating and site survey. Highlights: Novel application of industry 3D seismic datasets to construct continuous high-resolution bathymetry covering 6500 square km seabed. Identifying and extensive and complex submerged coastal landscape situated at 75 m below present sea level. Assigning a probable timing of formation to Marine Isotope Stage (MIS) 3. Formation of submerged MIS 3 coastal landscapes overlaps with the known onset of occupation of NW Australia ∼(50, 000 yrs BP).